Pemberdayaan Ibu Rumah Tangga Melalui Ekonomi Kreatif Agroindustri Jamur Tiram - Sri Sumarliani; Sri Hastuti (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Women who become housewives make some women only rely on income from their husbands as the head of the family. Meanwhile, women also have a big role in poverty reduction activities through the empowerment of housewives to improve the welfare of their families by carrying out productive business activities.  This activity aims to empower housewives to improve the family economy through processed raw oyster mushrooms into one processed product such as chips, noodles, meatballs, oyster mushroom broth that can be consumed by the community and can be optimally developed into preparations with a high selling value. The method used is socialization and awareness that innovation in processed oyster mushrooms through the empowerment of housewives who are members of the oyster mushroom farmer group "Manut" by facilitating education and training, as well as facilitating to communicate, coordinating with the Lumajang Regency Health Office and the Lumajang Regency Trade Office collaborated to expand marketing and make oyster mushrooms into superior production. The Manut Oyster Mushroom Farmer Group turns raw materials into processed materials so that the mushrooms do not rot quickly and the processed oyster mushrooms that have been packaged become durable. In terms of economic value, processed mushrooms have basically experienced an increase in income and are also related to managing or combining to determine processed priorities in order to maintain and improve life with the creative economy.